Dose Area Product Performance in Fluoroscopy as Supporting Modalities Lithrotripsi Extracorporeal Shock Wave (ESWL) Action for Kidney Stone Localization Resolution - Siti Daryati; M. Irwan Katili; Sri Mulyati (Poltekkes Kemenkes Semarang, 2014)
This is an observational method with a quantitative approach to study the magnitude of dose area product who received ESWL patients and the level of safety in accordance with the rules of radiation safety in the use of X-ray. Processing and analysis of the data is done by calculating the dose area product ( DAP ) received by the patients at each exposure based on the thickness of the patients were detected with the TLD. Comparison is done with the use of standard flouroscopy examination. Result shows that 10 cm material thickness in 0.008 minutes results 187mGy.cm2 and 5095 mGy.cm2 DAP in 5 minutes. While in 20 cm phantom thickness and in 0.008 minutes result 424 mGy.cm2 and DAP obtained in 5 minutes is 2 20912 mGy.cm. The use of fluoroscopy on ESWL in Dr . Kariadi hospital is still within the safe limits: less than 100 mGy / min , the dose rate exposure on a 10 cm phantom thickness is 3.38 mGy / min and in 20 cm phantom thickness is 13.89 mGy / min , exposure dose rate per minute on the phantom thickness of the 23 cm is 17.03 mGy / min and the rate of patient exposure dose obtained by the observation of 17.61 mGy / min.